2006
DOI: 10.1097/01.aog.0000192512.03576.da
|View full text |Cite
|
Sign up to set email alerts
|

Is Liquid-Based Pap Testing Affected by Water-Based Lubricant?

Abstract: II-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 8 publications
2
20
1
1
Order By: Relevance
“…gel after the collection and before being placed in the cervical cytology solution. 7 No interference in cervical cytology evaluation from the gel was shown. This finding is in agreement with our results that the gel had little effect on smear interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gel after the collection and before being placed in the cervical cytology solution. 7 No interference in cervical cytology evaluation from the gel was shown. This finding is in agreement with our results that the gel had little effect on smear interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] However, it has also been shown that lubrication of the external surfaces of the speculum blades with a small amount of gel does not significantly reduce patient discomfort during speculum examination. 8 Although increasing the amount of gel lubricant should reduce the discomfort associated with speculum insertion, data are lacking concerning the effects on the Pap smear from contamination of the cervix by greater than normal amounts of gel lubricant.…”
Section: Lubricating Gel Contamination Of the Cervix Can Adversely Afmentioning
confidence: 99%
“…5 However, there is convincing evidence in the literature suggesting that water-based lubricants do not obscure cytology results when used in small amounts before speculum insertion. [1][2][3] Nevertheless, there are several reports suggesting that water-based lubricants might affect the LBC specimen preparation procedure when direct contamination occurs. 9 -12 Although direct contamination of the liquid in the vial is not a concern in clinical practice, we cannot exclude the possibility of an indirect contamination of the specimen collected from cervix (if the lubricant sticks to cervix).…”
Section: Discussionmentioning
confidence: 99%
“…There is convincing evidence in the literature supporting that lubrication of the speculum does not alter the cytological interpretation of cervical cytology specimens. [1][2][3][4][5] Moreover, a recent study suggested that topical application of anesthetic cream to the genital mucosa of postmenopausal women before a vaginal examination significantly reduces the pain associated with speculum application. 6 The aims of this study were to investigate the effects of lubrication during speculum insertion on pain perceived by women and the quality of the Papanicolaou test specimen.…”
mentioning
confidence: 99%
“…3 In the Swedish study, women who received paroxetine in early pregnancy had increased risk of having an infant with a cardiac defect compared to the entire registry population (2% of paroxetineexposed infants had defects vs 1% of all infants, odds ratio [OR] 1.8, 95% confidence interval [CI] 1. 1-2.8).…”
mentioning
confidence: 99%